Dimensione “pubblica” del magistero pontificio: frammenti di dottrina sociale sull’economia mondiale (Stato, Chiese e pluralismo confessionale, 2012)
SOMMARIO: 1. Trasformazioni economiche e dinamiche sociali − 2. Centralità della persona umana nella dottrina sociale cattolica − 3. Luci ed ombre del sistema economico contemporaneo − 4. Esigenze di regolamentazione dei mercati internazionali − 5. Il primato del “bene comune” sugli interessi particolari.ABSTRACTSize "public" of the papal magisterium: fragments of social teaching on the world economyThe Catholic Church for several years devoted particular attention to the economic processes of the world, drawing on ideas that enrich the overall picture of its "social doctrine". In this case, the papal teaching proved to be quite sensitive to the phenomena of globalization that are investing also global economic system. This paper intends to analyze some key points of the papal reflection on the subject, highlighting the relevance "public", which is gradually to assume the contribution of Catholic social teaching around the overall dynamics of the global economy.PAROLE CHIAVE: Economia – Globalizzazione - Sistema economico mondiale - Dottrina sociale cattolica - Magistero pontificio